RESPONSE OF TWO SPECIES OF ATRIPLEX TO DIFFERENT SOWING DATES OF NORTHEN IRAQ - K. Kasim; M. J. AbDul Rahman; Younis H. Kasim (Mesopotamia Journal of Agriculture, 2017)
This study was conducted at Al-Rasheedia Research Station 5 Km North of Mosul city in plastic pot and placed under natural conditions and watered for the two consecutive growing seasons 2008/2009 and 2009/2010 to study the effect of five sowing dates (1st November. 15th November. 1st December. 15th December. 1st January) on two species of Atriplex; Atriplex halimus and Atriplex lentiformis. The data was analyzed as a factorial experiment in a completely Randomized Design (CRD) with six replicates. Results showed significantly superiority of the first date of sowing 1st November on other dates. Height of plant. root depth and root diameter for the two growing seasons 2008/2009 and 2009/2010. Also on the dry weight of leaves. stems. roots and plant for the two growing seasons. High values were recorded under the first date of sowing 1st November but the low values were recorded under the last date of sowing 1st January for all characters. Also. the results showed significantly superiority of Atriplex halimus on Atriplex lentiformis for all characters under study. There was a significant interaction between the two growing seasons in height of plant. root depth. root diameter and plant dry weight